2003
DOI: 10.1122/1.1595099
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic theory of linear, entangled polymer chains under rapid deformation including chain stretch and convective constraint release

Abstract: A refined version of the Doi and Edwards tube model for entangled polymer liquids is presented. The model is intended to cover linear chains in the full range of deformation rates from linear to strongly nonlinear flows. The effects of reptation, chain stretch, and convective constraint release are derived from a microscopic stochastic partial differential equation that describes the dynamics of the chain contour down to the length scale of the tube diameter. Contour length fluctuations are also included in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
555
5
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 460 publications
(591 citation statements)
references
References 26 publications
30
555
5
1
Order By: Relevance
“…In such cases, a nonuniform tensile flow acts on the polymeric physical network, where topological links are formed as a result of chain entanglement (a polymeric physical network under very rapid deformation can be regarded as polymer gel). Although the behavior of polymer gels under rapid deformation has been discussed by many authors, [49][50][51][52][53] we are not aware of a solution for the specific problem occurring in the electrospinning process, namely local deformation of an elongated network of semidilute polymer solution.…”
Section: Reviewmentioning
confidence: 99%
“…In such cases, a nonuniform tensile flow acts on the polymeric physical network, where topological links are formed as a result of chain entanglement (a polymeric physical network under very rapid deformation can be regarded as polymer gel). Although the behavior of polymer gels under rapid deformation has been discussed by many authors, [49][50][51][52][53] we are not aware of a solution for the specific problem occurring in the electrospinning process, namely local deformation of an elongated network of semidilute polymer solution.…”
Section: Reviewmentioning
confidence: 99%
“…This constraint release process provides a second relaxation mechanism, commonly modeled as a local sideways hop of the tube at each constraint release event [3][4][5][6]. Accounting for constraint release has been essential in understanding the experimental lack of shear banding in strong flows of monodisperse melts [5,6]. It is also crucial in most industrial polymers, where polydispersity of chain length, and chain branching, result in a wide spectrum of constraint release rates.…”
mentioning
confidence: 99%
“…Here, we have used the same definition of constraint release rate S as used by Graham et al [6], and retain the same prefactors as suggested by their equation for constraint release events of a tube. The second time scale is the constraint release Rouse time for the whole thin tube (comprising Z L thin tube segments), which is, similarly,…”
mentioning
confidence: 99%
See 2 more Smart Citations